The costs and benefits of packaging waste management systems in Europe: the perspective of local authorities. Issue 5 (4th May 2017) - Ferreira, S.; Cabral, M.; da Cruz, N.F.; Simões, P.; Marques, R.C.
Abstract : Local authorities are generally in charge of household packaging waste management operations, particularly in countries with Green Dot schemes or similar extended producer responsibility systems. This leads to the need of establishing a system of financial transfers between the packaging industry and the local authorities (regarding the costs involved in selective collection and sorting). In the present study, the costs and benefits of recycling, from the perspective of local authorities, are compared for Portugal, Belgium and Italy (in Lombardia region), adopting the same economic–financial methodology. The results show that the industry is not paying the net cost of packaging waste management. If the savings attained by diverting packaging waste from other treatment operations are not considered, it seems that the industry should increase the financial support to local authorities. However, if the avoided costs with other treatments are considered as a benefit for local authorities, the costs are generally outweighed by the benefits, and the financial support could, therefore, be reduced.